Plant Physiological Aspects of Phenolic Compounds 2019
DOI: 10.5772/intechopen.83815
|View full text |Cite
|
Sign up to set email alerts
|

Shikimic Acid Pathway in Biosynthesis of Phenolic Compounds

Abstract: Phenolic compounds are secondary metabolites found most abundantly in plants. These aromatic molecules have important roles, as pigments, antioxidants, signaling agents, the structural element lignan, and as a defense mechanism. The expression of phenolic compounds is promoted by biotic and abiotic stresses (e.g., herbivores, pathogens, unfavorable temperature and pH, saline stress, heavy metal stress, and UVB and UVA radiation). These compounds are formed via the shikimate pathway in higher plants and microor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 35 publications
6
114
0
2
Order By: Relevance
“…A recent study has revealed that high levels of these metabolites at the site of pathogen invasion can restrict or slow the growth of the pathogen [ 7 ]. The shikimic acid pathway consists of many sequential enzymatic steps, each reaction produces different metabolites that play an important role as branch point compounds serving as factors that induce the synthesis of various phenolic compounds in the plant [ 48 ]. Seven enzymes could intervene in this pathway for the development of the majority of secondary metabolites depending on the elicitor molecules [ 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has revealed that high levels of these metabolites at the site of pathogen invasion can restrict or slow the growth of the pathogen [ 7 ]. The shikimic acid pathway consists of many sequential enzymatic steps, each reaction produces different metabolites that play an important role as branch point compounds serving as factors that induce the synthesis of various phenolic compounds in the plant [ 48 ]. Seven enzymes could intervene in this pathway for the development of the majority of secondary metabolites depending on the elicitor molecules [ 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The shikimic acid pathway consists of many sequential enzymatic steps, each reaction produces different metabolites that play an important role as branch point compounds serving as factors that induce the synthesis of various phenolic compounds in the plant [ 48 ]. Seven enzymes could intervene in this pathway for the development of the majority of secondary metabolites depending on the elicitor molecules [ 47 , 48 , 49 ]. From this, it can be suggested that the difference in the expression of phenolic compounds in the leaves of tomato seedlings between alginates and oligoalginates could be explained by the distinct target of the enzymatic reactions stimulated by each elicitor in the shikimate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The phenylpropanoid pathway starts with the amino acid phenylalanine (Phe), derived from the shikimate pathway, which in plants is located in the chloroplasts [31].…”
Section: Plant Secondary Metabolism: the Phenylpropanoid Pathway As Amentioning
confidence: 99%
“…In 1936, Haworth introduced lignans as a group of plant-based compounds consisting of β-β -linked dimeric phenylpropane units ( Figure 1) [1]. Similar to other natural phenolics such as stilbenes and flavonoids, lignans are formed through the shikimic acid pathway [2]. Lignans have attracted great interest in research as they have a number of health benefits, such as being strong antioxidants, lowering the risk of coronary heart disease, and having neuroprotective effects and anticancer properties [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, they were chosen to study the selectivity in the oxidation reactions (epoxidation) with substrates containing free phenolics (1 and 3) compared to protected (methoxylated) derivatives (2 and 4). Secondly, we wanted to study the outcome of the epoxidation reaction in the presence of a primary hydroxyl (1)(2), carboxylic acid (3) and methyl ester (4). A subclass of lignans called norlignans are dimers composed of a phenylpropane unit and a phenylethane unit coupled through a β-β´ linkage (Figure 1).…”
Section: Introductionmentioning
confidence: 99%